Freedom of Expression: The Very Modern Practice of Visiting a Shinto Shrine - Nelson, John K. (Japanese journal of religious studies, 1996)
Utilizing extended fieldwork, interviews, and cross-cultural reference with other religious sites, the present study examines why the practice of visiting Shinto shrines continues to hold salience for millions of contemporary Japanese. Observations show that a majority of individuals coming to one particular shrine, Kyoto's Kamigamo Jinja, generally comply with the spiritual and visual ideology of the site, yet rarely describe themselves as "worshippers" or even know the name of the principal deity. Shrine visits are neither coerced nor made as a rational means to an end; instead, visitors are generally drawn to the shrine as a repository of cultural heritage within a tranquil "natural" setting. Because contemporary shrines generally do not impose guidelines for a shrine visit, nor do priests attempt to monitor behavior, the paper concludes that the shrine's relevance lies not in its message but in the considerable freedom it provides individuals to use its precincts for spiritual, habitual, and recreational pursuits.